(untitled) (Chemical Engineering Research Bulletin, 2023)
Syngas or synthesis gas is very demanding gas mixture mainly containing Hydrogen (H2) and Carbon monoxide (CO) gas which is used in producing of Hydrogen fuel, Methanol, Ammonia. Syngas can be produced from renewable resource like biomass. Sawdust is one of the common, less costly waste biomass found in sawmill. Generally, sawdust is used for burning to make heat for cooking but pyrolysis and Gasification process can turn it as biofuel which is more economic and have versatile usability. By simulating the gasification of sawdust through Aspen plus software, the amount of formation of syngas can be calculated. R-yield or yield reactor is used to calculate the production of syngas for 100% conversion of Biomass into Biofuel as R-yield as ideal reactor, need to specify the basic yield based on ultimate analysis of sawdust. R-Gibb reactor is used to calculate the total heat required completing the whole process found in combustion reaction and dryer is used to dry wet biomass using combustion heat. Produced syngas contains not only H2, CO rather than the mixture of H2, CO, CO2, CH4, C2H4, N2, NH3, H2S, H2O, solid Carbon and ash content. The simulation conducted on gasification clearly gives the information that’s by entering about 1000 kg sawdust in a gasifier with 1358 kg air, temperature raised about 700° C, after thermal conversion about 2218.5 kg syngas, 111.2 kg H2O and 28.3 kg ash would have found. Primarily, simple flash separator is used to calculate the separated ash content and solid carbon. Cryogenic distillation can be used for individual gas separation. Chemical Engineering Research Bulletin 23(2023): 41-45